The preservation of right cingulum fibers in subjective cognitive decline of preclinical phase of Alzheimer’s disease - Sun, Yu; Qiao, Yanan; Guo, Jing; Hou, Wenjie; Chen, Yaojing; Peng, Dantao (Frontiers in Aging Neuroscience, 2023)
Subjective cognitive decline (SCD) with a positive amyloid burden has been recognized as the earliest clinical symptom of the preclinical phase of Alzheimer’s disease (AD), providing invaluable opportunities to improve our understanding of the natural history of AD and determine strategies for early therapeutic interventions. Here, the microstructure of white matter in patients showing SCD in the preclinical phase of AD (SCD of pre-AD) was evaluated using diffusion images, and voxel-wise fractional anisotropy (FA), mean diffusivity (MD), and axial and radial diffusivities were assessed and compared among participant groups. Significant clusters in the tracts were extracted to determine their associations with alterations in the cognitive domains. In conclusion, we found that individuals showing SCD of pre-AD may have subclinical episodic memory impairment associated with the global amyloid burden. Meanwhile, increased white matter microstructural integrity in the right cingulum (cingulate and hippocampus) may indicate compensation for short-term episodic memory in individuals with SCD of pre-AD in comparison with individuals with AD and healthy elderly individuals.